Self-Efficacy Mahasiswa PGSD Pada Perkuliahan Daring Di Era New Normal - Pagarra, Hamzah; Irfan, Muhammad; Raihan, Siti (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
Disruptive innovation is a challenge for universities in preparing graduates who have superior human resources. PGSD students need to understand themselves and know the pattern of self-mastery or self-efficacy in order to optimize the development of their potential in achieving lecture targets. Achieving the target of online lectures in the new normal era requires the role of students as learners. The importance of this study aims to reveal the dimensions of self-efficacy of PGSD students who play a role in online lectures in the new normal era. This research was carried out with a qualitative descriptive method. The results reveal the dimensions of self-efficacy of PGSD students, consisting of: efficacy to influence decision making, instructional self-efficacy, disciplinary self-efficacy, efficacy to enlist lecturer involvement, efficacy to enlist community involvement and efficacy to create a positive learning. It can be concluded that there are 6 dimensions of self-efficacy of PGSD students with very good and good categories that play a role in the achievement of online lectures in the new normal era.